Using social media to engage and develop the online learner in self-determined learning - Lisa Marie Blaschke (Research in Learning Technology, 2014)
Social media technology provides educators with an opportunity to engage learners in the online classroom, as well as to support development of learner skills and competencies. This case study explores the role of social media in promoting cognitive and meta-cognitive learner development while using a heutagogical teaching and learning approach. Research was conducted using questionnaires and interviews and incorporated the perspectives of both students and instructors on the use of social media in the online classroom and how media influenced interaction and learner development. Results indicate that students perceived specific social media (Google Docs, mind mapping and e-portfolio software) in conjunction with a unique learning activity as influencing specific cognitive and meta-cognitive skills (constructing new knowledge, reflecting on course content, understanding individual learning process). Research also indicated an increase in student familiarity with using social media and student research skills. This paper presents the findings from the case study, as well as general guidance to instructors for incorporating social media in the online classroom.